Blue monkeys' utilization of five tree species in relation to the abundance of each tree species : teclea nobilis, Elaeodendron buchananii, Species 1, Grewia bicolor and Ficus sycamorus - Ahlbäck, Lina (SLU/Dept. of Animal Environment and Health (until 231231), 2008)
This paper is a part of a larger study with the purpose of investigating foraging behaviour and feeding preferences of blue monkeys' (Cercopithecus mitis stuhlmanni) in the study area. The study took place in the Sabaringo forest just north of the Masai Mara National Reserve, Kenya, where a group of 50 blue monkeys live. In July 2006 the foraging and positioning preferences of lactating and non-lactating females regarding the different tree species in the forest were studied by a group of other Swedish students. To determine if these trees are rejected or preferred, a total inventory of the trees in the area was carried out by me and a fellow student in March 2007. We compared our results with previously collected data of the preferences of the monkeys. My thesis focuses on five of the ten most preferred trees whereas the other five are discussed in the corresponding paper by Kempe. A total of 10 260 trees were counted and 50 different species could be identified. The most common of my focal tree species was Teclea nobilis making up 35 % of the total number of trees but used for positioning only 15 % of the observation time. The species that were used for feeding in the highest extent was Grewia bicolor, especially by the lactating females who often ate the fruits from it. In relation to the percentage of the forest biomass that this species made up (calculated from its stem area) it was eaten from almost six times more than expected from its abundance. Ficus sycamorus had an even higher ratio between occurrence and usage as food, more than 1:30 counted by number of trees or stems. Because it is one of the largest trees, the number was much lower (about seven) counted by area cover. The species only contributed to approximately 0.2 % of the number of trees or stems and a little over 1 % of the total biomass counted by stem area. In addition to these three species Elaeodendron buchananii and an unclassified species (Species 1) were also studied in detail and are presented in this paper.